2018
DOI: 10.1002/jor.23903
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic loaded calcium sulfate bead and pulse lavage eradicates biofilms on metal implant materials in vitro

Abstract: Pulse lavage (PL) debridement and antibiotic loaded calcium sulfate beads (CS-B) are both used for the treatment of biofilm related periprosthetic joint infection (PJI). However, the efficacy of these alone and in combination for eradicating biofilm from orthopaedic metal implant surfaces is unclear. The purpose of the study was to understand the efficacy of PL and antibiotic loaded CS-B in eradicating bacterial biofilms on 316L stainless steel (SS) alone and in combination in vitro. Biofilms of bioluminescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 34 publications
4
26
1
Order By: Relevance
“…The independent use of pulsed lavage against S. aureus biofilms appeared to remove most of the biofilm cells and biomass in our experiments. This contrasts with previous studies that reported a 1 to 2 log 10 reduction in cell numbers following pulsed lavage (17,18,20). This discrepancy between our results and previous studies may be due to differences in strains, material surfaces or culture conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The independent use of pulsed lavage against S. aureus biofilms appeared to remove most of the biofilm cells and biomass in our experiments. This contrasts with previous studies that reported a 1 to 2 log 10 reduction in cell numbers following pulsed lavage (17,18,20). This discrepancy between our results and previous studies may be due to differences in strains, material surfaces or culture conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…This combination of pulsed lavage with antibiotics at concentrations compatible with a parenteral administration to simulate PJI has not been previously reported. Knecht et al published on the combination of pulsed lavage and incubation with tobramycin- and vancomycin-loaded calcium sulfate beads, showing a strong synergy ( 20 ). However, the antibiotic concentrations eluted in the culture medium were not determined, limiting the extrapolation of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did find evidence that the method might reveal locations which might be more prone to harboring biofilms. For example, cases 12 and 13 showed preferential biofilm formation around the femoral head non‐articulating ‘rim skirt’ surface and surface features and a similar pattern was seen in a biofilm grown in vitro and a previous explant case , suggesting factors such as surface roughness or the non‐abating nature of the rim skirt played a role in the harboring of bacteria. Such information may provide insight into the development of orthopaedic components with surface modifications to reduce bacterial attachment and biofilm formation.…”
Section: Discussionmentioning
confidence: 71%
“…The innovation of the DAPRI technique stays only on the combination of previously well described techniques which combine the known microbicidal power of the aforementioned procedures having a well-documented high synergistic power. 47,48 The addition of calcium sulphate beads constitutes a remarkable innovation as it allows to create an environment unfavorable to bacterial proliferation and biofilm synthesis for a period of time up to 40 days; [49][50][51] moreover, these beads are completely re-absorbable, leaving no substrate for the proliferation of pathogens. 1 great advantage of calcium sulphate beads is their flexibility in terms of being mixed with antibiogram driven antibiotics: heat labile antibiotics can be added because there are no exothermic reactions during calcium sulphate beads preparation on the back table.…”
Section: Discussionmentioning
confidence: 99%